Pengaruh Latihan Rondo Terhadap Peningkatan Keterampilan Passing Pemain Sepakbola Usia 13 Tahun - Riyadh Almiqdaad; Yadi Sunaryadi; Ridha Mustaqim (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effect of rondo training on improving the passing ability of 13-year-old soccer players at SSB Sascwo Bandung. This study uses a quantitative method with an experimental approach and a One Group Pretest-Posttest Design. The research sample consisted of 24 13-year-old soccer players selected using a purposive sampling technique. The research instrument used the Passing Grid Test to measure the players' passing ability before and after treatment. The treatment given was 12 rondo training sessions in one month with a frequency of three times a week. Data analysis used the Shapiro-Wilk normality test and the Paired Sample T-Test hypothesis test. The results showed an increase in the average passing score from 92.29 in the pretest to 113.96 in the posttest with an increase of 21.67 points. The results of the hypothesis test showed a significance value of 0.000 <0.05, which means there is a significant effect of rondo training on improving the passing ability of 13-year-old soccer players. Thus, rondo drills have been shown to be effective as a training method to improve the passing ability of 13-year-old soccer players. Keywords: Ball Passing Skills, Rondo Training, 13-Year-Old Players, Soccer